Adaptive-passive tuned mass damper for structural aseismic protection including soil–structure interaction - Wang, Liangkun; Shi, Weixing; Zhou, Ying (Soil dynamics and earthquake engineering (1984), 2022)
As one of the most traditional vibration mitigation devices, tuned mass dampers (TMDs) are applied widely in aseismic protection of building structures. The control effect of a passive TMD is depended on its parameters, especially the frequency ratio. Nevertheless, passive TMDs are high sensitive to the frequency detuning issue, and a mistuned TMD will lose its aseismic protection. Soil-structure interaction (SSI) will deviate the structural frequency and lead to a mistuned TMD. Besides, different soil conditions will lead to different frequency deviations of the primary structure. However, it may be difficult to obtain parameters of the soil exactly. To solve this problem, a recently developed adaptive-passive eddy current pendulum TMD (APEC-PTMD) is applied to a benchmark 40-story tall building including SSI in this study, and four different soil conditions are considered. The APEC-PTMD can identify the optimal TMD frequency in the building with different soil types, and then retune itself through adjusting the pendulum length, and also the air gap between the conduct plate and permanent magnets to reset its damping ratio. Therefore, no prior knowledge of the soil condition is needed for the APEC-PTMD. To verify the aseismic protection effect, 44 far-field earthquake excitations are chosen, and two passive TMDs are used for comparison, while one is optimized for the base-fixed structure and the other is optimized based on the dense-soil model. The passive TMD will become mistuned when SSI is considered or soil parameters are changed, while APEC-PTMD can adapt to the structural dominant frequency with different SSI. Therefore, it always works as a passive TMD with well-tuned parameters. Results show that the APEC-PTMD has a better aseismic protection than the passive TMD, especially in the soft-soil model, and it has an excellent control effect compared to the without TMD case at the same time. •An adaptive-passive eddy current tuned mass damper (APEC-TMD) with variable pendulum length and damping ratio is proposed.•The APEC-TMD is applied to a benchmark high-rise building considering soil-structure interaction (SSI).•The APEC-TMD can identify the dominant frequency of the building with different SSI condition.•The APEC-TMD has the best structural aseismic protection performance compared to passive TMDs.